Carta de Roberto H. Todd a Samuel R. Quiñones - Todd, Roberto H.; Quiñones, Samuel R. (My University, 1936)
Posibilidades para donar los bienes de Mariano Abril a l Ateneo Puertorriqueño
Keywords: Abril Ostalo, Mariano, 1861-1935